PMMA brush-modified graphene for flexible energy storage PVDF dielectric films. (January 2023) - Wang, Zhen; Xue, Wenqing; Yang, Yongzhi; Li, Yuchao; Wang, Shuangshuang; Zhan, Yanhu; Li, Wei; Hao, Jigong; Zha, Jun-Wei; Liu, Chen; Cao, Yulin; Lu, Zhouguang
Abstract: Flexible dielectric materials are highly desirable in many electric/electronic devices for energy harvesting applications, but they usually suffer from the paradox of high dielectric constant and large breakdown strength, thereby reducing the overall energy storage capacity and mechanical strength with large filler loadings. In this work, poly(methyl methacrylate) (PMMA) brush-modified graphene (rGO-g-PMMA) was successfully introduced into poly(vinylidene fluoride) (PVDF) matrix via solution casting method. The PMMA brush-modified graphene for one thing promoted graphene distribution in the PVDF matrix, for another, it effectively limited carrier leakage of conductive graphene by forming a thin insulating PMMA layer. Therefore, the dielectric constant of rGO-g-PMMA/PVDF films was obviously increased, while the dielectric loss was distinctly suppressed with a small addition of the "core-shell" like rGO-g-PMMA. What's more, the breakdown strength of composites increased with rGO-g-PMMA loadings up to 0.2 wt%, accompanied by a 157% increase in energy density of FGM-0.2 composite to that of neat PVDF. In addition, the obtained rGO-g-PMMA/PVDF dielectric films possessed improved thermal stability and mechanical strength due to the homogeneous dispersion and good interfacial adhesion of rGO-g-PMMA within PVDF matrix. Such study provided a new strategy in obtaining flexible, high strength and large energy storage dielectric films. Graphical abstract: Image 1 Highlights: Improved dielectric and energy storage capacity of flexible PVDF dielectric films are achieved via incorporating PMMA brush-modified graphene. The dielectric loss is effectively suppressed due to the attachment of PMMA brushes onto graphene surface. The thermal stability, mechanical strength and resistance to electrical breakdown of the dielectric films are simultaneously enhanced.